Expression of CD69 on T-cells from HIV-1-infected children and adolescents increases with increasing viral load - Böhler, Thomas; Walcher, Judith; Hölzl-Wenig, Gabriele; Schnitzler, Paul; Geiss, M.; Buchholz, Bernd; Linde, R.; Rütschle, H.; Debatin, Klaus-Michael (European journal of pediatrics, 1999)
We evaluated the use of a whole-blood assay that measures spontaneous and activation-induced CD69 expression on peripheral blood T-cells in vitro for assessment of T-cell function in HIV-1-infected paediatric patients. Heparinized venous blood from 28 HIV-1 positive children and adolescents and 23 healthy controls was incubated for 4 h with or without 5 microg/ml phytohaemagglutinin (PHA). Thereafter, analysis of CD69 expression on CD4+ and CD8+ T-cells was done by flow cytometry; simultaneously we determined CD4+ T-cell counts and plasma HIV-1 viral load. Neither spontaneous nor PHA-induced CD69 expression differed significantly between HIV-1 positive patients and healthy controls. However, T-cells from HIV-1 positive patients with plasma HIV-1 viral load levels above 70x10(3) copies/ml showed a higher spontaneous CD69 expression than T-cells from patients with lower plasma viral load levels in different stages of the disease. Antiretroviral treatment in four patients reduced spontaneous CD69 expression in CD4+ T-cells and PHA-induced CD69 expression in CD4+ and CD8+ T-cells significantly after 8 weeks of therapy. Conclusion Spontaneous and activation-induced expression of the early (activation) antigen CD69 on peripheral blood T-cells does not distinguish HIV-1 positive patients from HIV-1 negative healthy controls and is not correlated with peripheral blood CD4+ T-cell counts. This test may not be a reliable marker for functional T-cell deficiency during early stages of HIV disease. Increased spontaneous as well as PHA-induced CD69 expression on T-cells from HIV-1-infected children and adolescents in vitro may rather reflect HIV-induced pre-activation of T-cells in vivo.
Gesehen am 09.04.2021